2006
DOI: 10.1016/j.febslet.2006.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Reversible skeletal neuromuscular paralysis induced by different lysophospholipids

Abstract: Lysophosphatidylcholine rapidly paralyses the neuromuscular junction (NMJ), similarly to snake phospholipase A2 neurotoxins, implicating a lipid hemifusion-pore transition in neuroexocytosis. The mode and kinetics of NMJ paralysis of different lysophospholipids (lysoPLs) in high or low [Mg 2+ ] was investigated. The following order of potency was found: lysophosphatidylcholine > lysophosphatidylethanolamine > lysophosphatidic acid > lysophosphatidylserine > lysophosphatidylglycerol. The latter two lysoPLs cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…These neurotoxins have been suggested to bind to the so-called active zones, i.e. those microdomains of the presynaptic membrane where synaptic vesicle neurotransmitter release takes place [16,50,53]. An alternative suggestion has been that they act on the internal membrane layer of synaptic vesicles, once they become exposed to the medium following exocytosis [54].…”
Section: Membrane Damagementioning
confidence: 99%
“…These neurotoxins have been suggested to bind to the so-called active zones, i.e. those microdomains of the presynaptic membrane where synaptic vesicle neurotransmitter release takes place [16,50,53]. An alternative suggestion has been that they act on the internal membrane layer of synaptic vesicles, once they become exposed to the medium following exocytosis [54].…”
Section: Membrane Damagementioning
confidence: 99%
“…CGN neurons are highly sensitive to SPANs and develop a well-defined bulging at axon and dendrite terminals within few minutes from toxin addition; such morphological alteration is accompanied by cytosolic calcium increase at nerve terminals and glutamate release from neurons (Rigoni et al 2004(Rigoni et al , 2007. These effects are mimicked by the addition of an equimolar mixture of the PLA 2 hydrolysis products, lysophosphatidylcholine (LysoPC) + oleic acid, indicating that these molecules are the biochemical mediators of SPAN action (Rigoni et al 2005;Caccin et al 2006). Of the two lipid molecules, LysoPC was shown to be most effective (Caccin et al 2006(Caccin et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…These neurotoxins are abbreviated here as snake pre-synaptic PLA 2 neurotoxins (SPANs). The role of their PLA 2 enzymatic activity in the blockade of the neuromuscular junction (NMJ) has been long debated (Rosenberg 1997;Kini 2003;Gutiérrez et al 2006), but recent results demonstrated that their phospholipid hydrolysis products, lysophospholipids (LysoPLs) and fatty acids (FAs), are sufficient to cause NMJ paralysis with the associated pathological changes (Rigoni et al 2005;Caccin et al 2006). Therefore, to define the pathological action of SPANs it is necessary to analyse their PLA 2 activity in vivo as a function of time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lysophospholipids induce a membrane curvature which favors membrane fusion of synaptic vesicles and, at the same time, inhibits endocytosis, thus explaining the typical features shown by electron microscopy, i.e., synaptic vesicle depletion and O-shaped plasma membrane figures. Indeed all the morphological and functional alterations induced by these snake neurotoxins can be reproduced by the addition of a mixture of fatty acids and lysophospholipids (Rigoni et al 2005;Caccin et al 2006). High amounts of lysophospholipids, such as those produced by Snake Venoms DOI 10.1007/978-94-007-6648-8_26-1 # Springer Science+Business Media Dordrecht 2015 these snake neurotoxins, destabilize membranes, and it was found that bulges are sites of calcium influx from the extracellular medium in the cytosol, which is then accumulated inside mitochondria causing loss of their membrane potential (Rigoni et al 2007(Rigoni et al , 2008.…”
Section: Neurotoxic Snake Pla2smentioning
confidence: 99%